Enhancing Image Processing Capabilities through Advanced Approximate Multipliers - Vadlamudi, Sreelakshmi; Yarlagadda, Syamala; R. Madhu (International Journal of Computational and Experimental Science and Engineering, 2025)
This paper explores the utilization of advanced approximate multipliers and 4-2 compressors to enhance efficiency in digital image processing applications. As the demand for real-time image analysis grows, the need for computational efficiency becomes increasingly critical, especially in resource-constrained environments. The proposed approach employs approximate computing to achieve a significant reduction in processing speeds and energy consumption while maintaining acceptable levels of output quality. Through a systematic implementation using a Field-Programmable Gate Array (FPGA) and MATLAB, we demonstrate the effectiveness of approximation techniques in image blending and enhancement tasks. Experimental results highlight a favorable trade-off between accuracy and performance, indicating that minor inaccuracies do not significantly impair visual quality. Our findings suggest that integrating approximate computing methodologies can revolutionize various technology-driven industries by enabling faster and more efficient image processing solutions